2019
DOI: 10.1002/anie.201901511
|View full text |Cite
|
Sign up to set email alerts
|

Regioselectivity Switch in Palladium‐Catalyzed Allenylic Cycloadditions of Allenic Esters: [4+1] or [4+3] Cycloaddition/Cross‐Coupling

Abstract: The first Pd-catalyzed asymmetric allenylic [4+ +1] cycloaddition was successfully developed. Alternatively,tuning the Pd catalyst switched the reactivity toward an unprecedented [4+ +3] cycloaddition/cross-coupling. Ligands play av ital role in controlling the reaction pathway,a llowing highly selective access to different products from identical substrates.B iological evaluation of the obtained compounds led to the discovery of new antitumor targets.Apossible mechanism is proposed, suggesting two interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…In 2019, Shao and co-workers successfully developed aP dcatalyzed allenylic [4+ +3] cycloaddition/cross-coupling cascade (Scheme 26). [34] This unprecedented transformation displayed a broad scopew ith respect to allenyl acetates 101 and pyrazolones 102,p roviding an ovel family of dendralenes 103.T his reactioni si nitiated by Pd II -catalyzed intramolecular oxypalladation of 104 a,g enerating the seven-membered intermediate 104 b,w hich then undergoes ac ross-coupling reactionw ith another molecule of 101.F inally, trans-b-deacyloxypalladation generates the product 103 with exclusive formation of E isomer.…”
Section: Pd-catalyzed Cycloaddition Reactionsmentioning
confidence: 99%
“…In 2019, Shao and co-workers successfully developed aP dcatalyzed allenylic [4+ +3] cycloaddition/cross-coupling cascade (Scheme 26). [34] This unprecedented transformation displayed a broad scopew ith respect to allenyl acetates 101 and pyrazolones 102,p roviding an ovel family of dendralenes 103.T his reactioni si nitiated by Pd II -catalyzed intramolecular oxypalladation of 104 a,g enerating the seven-membered intermediate 104 b,w hich then undergoes ac ross-coupling reactionw ith another molecule of 101.F inally, trans-b-deacyloxypalladation generates the product 103 with exclusive formation of E isomer.…”
Section: Pd-catalyzed Cycloaddition Reactionsmentioning
confidence: 99%
“…In 2019, Shao and co-workers described a very interesting Pd-catalyzed asymmetric allenylic [4+1] formal cycloaddition leading to the synthesis of spirocyclopent-3-eneisoxazol-5-one derivative 58 (Scheme 9). 36 They demonstrated that in the case of pyrazolones the Pd catalyst could be tuned to switch the reactivity toward an unprecedented [4+3] or [4+1] cycloaddition/cross-coupling; only one example of the [4+1] reaction was given for an isoxazol-5-one. A possible mechanism is proposed, suggesting two interesting catalytic cycles for the cycloaddition of palladiumbutadienyl Int-59 with isoxazol-5-one via key intermediate Int-60 (Scheme 9).…”
Section: Isoxazol-5-ones As C-nucleophiles In Cyclization Processesmentioning
confidence: 99%
“…[b] ee [%] [d] 1 of pyrazolones.The relative and absolute configuration of the product 3p was determined by X-ray crystal analysis. [11] Next, we turned our attention to the allenylic [4+ +3] cycloaddition. We identified Pd(cod)Cl 2 /PPh 3 as the optimal catalyst for this reaction (see the Supporting Information for the details).…”
Section: Entrymentioning
confidence: 99%
“…We identified Pd(cod)Cl 2 /PPh 3 as the optimal catalyst for this reaction (see the Supporting Information for the details). [12] Ap ossible reaction mechanism is proposed (Scheme 4). This reaction is also the first catalytic [4+ +3] cycloaddition of pyrazolones.T aken together,t his study represents the first catalyst-controlled [4+ +1] and [4+ +3] cycloadditions of pyrazolones.T he structure of the product 4wwas determined by X-ray crystal analysis.…”
Section: Entrymentioning
confidence: 99%